THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLES AND MOTIVATION TOWARDS EMPLOYEE PERFORMANCE ON PT. BERLIAN PUTIH NUSANTARA - Hadi Kurniawanto (Jurnal Ekonomi, 2022)
This study aims to determine the influence of transformational leadership style and motivation on employee performance at PT. Diamond White Nusantara Persial and Simultaneously. This research method uses the Koralasional Quantitative Research Method with Pendektana Survey and uses Primary Data processed using SPSS. The population in this study is all employees of PT. Berlian Putih Nusantara amounted to 56 employees and samples were used for saturated samples, where the entire Population was Sampled. The results of this study show that there is an Influence of Transformational Leadership Style and Motivation on Employee Performance at PT. Berlian Putih Nusantara Both initially and simultaneously,